Spatial Distribution of Pacific Oyster (Crassostrea gigas) Population Related Environment Factor in Coastal Water of Pabean Ilir, Indramayu - Risma Qurani; Fredinan Yulianda; Agustinus Mangaratua Samosir (Jurnal Moluska Indonesia, 2020)
Pacific oysters (Crassostrea gigas, Thunberg, 1793) is a benthic organisme that tend to live and settle in the bottom. One of the pacific oyster habitat is Coastal Water of Pabean Ilir, Indramayu. The purpose of this study was to map spatial condition of the population related habitat of the oyster (Crassostrea gigas). The mapping were done with laptop, using Arc GIS. There were 15 points of sampling. The oyster population in Pabean Ilir can be categorized into three categories: low, medium, and high density. Based on the similarity of environmental characteristics the habitat were divided into four groups. Condition Coastal Water of Pabean Ilir such as temperature, salinity, pH, BOD, TSS, TDS, COD, and composition of substrate indicated Coastal Water of Pabean Ilir have compatibility optimum sufficient habitat to support the growth of pacific oyster